Tumor suppressive functions of LZTFL1 in hepatocellular carcinoma - Li S (OncoTargets and Therapy, 2019)
Shasha Li,* Jingjing Li,* Zujiang YuDepartment of Infectious Disease, The First Affiliated Hospital of Zhengzhou University, Zhengzhou 450052, Henan, People’s Republic of China*These authors contributed equally to this workBackground: Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related mortality worldwide. The poor survival may be due to tumor recurrence and metastasis. Growing evidence indicates that Leucine Zipper Transcription Factor-like 1 (LZTFL1) plays an important role in tumor progression of several cancers such as lung cancer and gastric cancer.Methods: Real-time PCR was performed to evaluate LZTFL1 expression level in HCC cell lines and patient specimens. The relationship between LZTFL1 expression and the clinicopathological data of the patients was analyzed. Stable cell lines with overexpressing LZTFL1 were set-up, and the cell proliferation, migration, and invasion abilities were analyzed. The protein expression was measured by Western blotting.Results: Here, we found LZTFL1 expression was decreased in human HCC specimens and HCC cell lines. Downregulation of LZTFL1 expression was correlated with tumor stage and metastasis. The ectopic overexpression of LZTFL1 inhibited cell proliferation, migration, invasion, and the expression of MMP9. In addition, LZTFL1 suppressed epithelial mesenchymal transition (EMT).Conclusion: Taken together, our results highlight the tumor suppressive role of LZTFL1 in HCC, suggesting that LZTFL1 may represent a potential therapeutic strategy for treating patients with HCC.Keywords: hepatocellular carcinoma, HCC, LZTFL1, migration and invasion, epithelial mesenchymal transition, EMT